Catálisis: an integrated approach. R.A. van Santen, P.W.N.M. van Leeuwen, J.A. Moulijn, B.A. Averill, editores. Elsevier, Amsterdam-Lausanne-New York-Oxford-Shannon-Singapure-Tokyo, 1999. - Shevtsova, Galina (2000)
El artículo no presenta resumen.